ECONOMIC STANDARD ANALYSIS OF FATTENING LOCAL LAMBS EXPERIMENT AT THE FIELDS COLLEGE OF AGRICULTURE AND FORESTRY, MOSUL UNIVERSITY - A. M. Hussein (Mesopotamia Journal of Agriculture)
The study aimed calculations of costs, incomes, profits, invested of one dinnar for three groups of local lambs which are feeding and fattening . on the three different rations in the level of protein (12, 13, 15% crude protein respectively). The optimum use of agricultural resources is generally regarded as one of the main tasks of farm management. It reduces farming cost on the one hand and increases profits or farm revenue on the other hand. This however, depends on the competence of farm management and the range of its application to the economic principles which include, some scales especially the farm management competence scale. This study was conducted at the fields of College of Agriculture and Forestry, Mosul University, and it included the economic standard analysis of the data collected from the lamb’s fallening local lambs experiment. The results showed that the third group which fed the third ration was the most profit-making compared wheb with the second and first lambs groups respectively. This profit ran up to 25173, 28302, 30281 Iraqi Dinars for each lamb in every group respectively. The invested Dinars profit reached to 1.366, 1.410 1.404 for the first, second and third groups of the lambs respectively.